Effect of skipping on body mass index, waist to hip ratio and muscle strength in overweight adolescent girls - Dhiya Fadhila Rahmah; Hadi Riyadi; Hardinsyah Hardinsyah (AcTion: Aceh Nutrition Journal, 2024)
Overweight problems in adolescents tend to increase, with obese nutritional status prevalence for Indonesian teenagers in group aged–13-15 and 16-18 years respectively 11,2% and 9,5%. This study aimed to analyze the effect of skip training on body mass index for age z-score (BAZ), waist-to-hip ratio (WHR), and muscle strength in overweight adolescent girls. The method of this research was a quasi-experimental design using a subject study of 28 female students, who were divided into two groups: those age between 15-18 years old. This study was conducted at Senior High School 1 West Sumatra and Batipuh from October to December 2023. The skipping group received 4-8 minutes of exercise 3 times per week for 8 weeks of intervention. The statistical analysis employed a paired t-test and simple linear regression test. The results of this study revealed that the skipping intervention had a significant effect on the reduction of BAZ (p<0,05; R2=0,286) and WHR (p<0,05; R2=0,174) in the skipping group compared to the control group. There was no significant difference in the muscle strength between the skipping and control groups (p>0,05; R2=0,049). In conclusion, skipping for a duration–4-8 minutes was conducted three times a week for 8 weeks, which reduced the value of BAZ and WHR in adolescent girls.